2010
DOI: 10.1128/jb.00698-10
|View full text |Cite
|
Sign up to set email alerts
|

Relatedness of Vibrio cholerae O1/O139 Isolates from Patients and Their Household Contacts, Determined by Multilocus Variable-Number Tandem-Repeat Analysis

Abstract: The genetic relatedness of Vibrio cholerae O1/O139 isolates obtained from 100 patients and 146 of their household contacts in Dhaka, Bangladesh, between 2002 and 2005 was assessed by multilocus variable-number tandem-repeat analysis. Isolate genotypes were analyzed at five loci containing tandem repeats. Across the population, as well as within households, isolates with identical genotypes were clustered in time. Isolates from individuals within the same household were more likely to have similar or identical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
76
2
2

Year Published

2012
2012
2016
2016

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(88 citation statements)
references
References 52 publications
8
76
2
2
Order By: Relevance
“…The identity of presumptive colonies was confirmed by using a battery of specific biochemical, serological, and molecular methods. Five loci for MLVA were analyzed by using methods described in previous studies (10)(11)(12). Genomic DNA of 76 confirmed V. cholerae strains along with eight reference strains were subjected to next generation whole-genome Illumina and hybrid Illumina/454 sequencing.…”
Section: Methodsmentioning
confidence: 99%
“…The identity of presumptive colonies was confirmed by using a battery of specific biochemical, serological, and molecular methods. Five loci for MLVA were analyzed by using methods described in previous studies (10)(11)(12). Genomic DNA of 76 confirmed V. cholerae strains along with eight reference strains were subjected to next generation whole-genome Illumina and hybrid Illumina/454 sequencing.…”
Section: Methodsmentioning
confidence: 99%
“…Multilocus variable-number tandem-repeat (VNTR) analysis (MLVA), a discriminating tool used to trace human V. cholerae infections (43) and resolve distinct populations of clinical isolates from different geographic regions (44), showed that V. cholerae BJG-01 is genotype 12.12.5.10, genetically distinct (see Table S2 in the supplemental material) from V. cholerae non-O1/O139 isolates of clinical and environmental origin, including representative 2010 Haitian V. cholerae isolates (27).…”
Section: Resultsmentioning
confidence: 99%
“…High secondary attack rates have been observed within households of cases (Mosley et al, 1965; McCormack et al, 1968; Mosley et al, 1968; Harris et al, 2008;Weil et al, 2009; Kendall et al, 2010). Although a common sources of exposure could account for many of these heavily infected households, studies of the time intervals between cases or that genotype infecting strains have found patterns of transmission consistent with ciclo corto transmission (Snow, 1855; Tamayo et al, 1965; Kendall et al, 2010).…”
Section: 2 Mathematical Models Of Cholera Transmissionmentioning
confidence: 99%
“…Although a common sources of exposure could account for many of these heavily infected households, studies of the time intervals between cases or that genotype infecting strains have found patterns of transmission consistent with ciclo corto transmission (Snow, 1855; Tamayo et al, 1965; Kendall et al, 2010). A tell-tale sign of ciclo corto transmission would be the rapid appearance of secondary cases consistent with the incubation period of cholera.…”
Section: 2 Mathematical Models Of Cholera Transmissionmentioning
confidence: 99%